2002
DOI: 10.1152/japplphysiol.01238.2001
|View full text |Cite
|
Sign up to set email alerts
|

Detection of porcine oleic acid-induced acute lung injury using pulmonary acoustics

Abstract: Rä sä nen, Jukka, and Noam Gavriely. Detection of porcine oleic acid-induced acute lung injury using pulmonary acoustics. J Appl Physiol 93: 51-57, 2002. First published March 1, 2002 10.1152/japplphysiol.01238.2001.-To evaluate the utility of monitoring the sound-filtering characteristics of the respiratory system in the assessment of acute lung injury (ALI), we injected a multifrequency broadband sound signal into the airway of five anesthetized, intubated pigs, while recording transmitted sound over the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 14 publications
3
11
0
Order By: Relevance
“…It is also in accord with the experimental evidence that the attenuation of sound introduced to the lung decreases when the lung is made edematous (4,13,15) and the well-known clinical observation that an increase in transmission of high-frequency sound occurs, giving rise to auscultatory signs such as "whispering pectriloquy" when the lung is consolidated in the presence of pneumonia (19). Furthermore, the strong frequency dependence of normalized attenuation indicates that the increase in attenuation with inflation at high frequencies is an intrinsic property of the lung tissue and not simply a manifestation of increased distance traveled by the sound waves.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It is also in accord with the experimental evidence that the attenuation of sound introduced to the lung decreases when the lung is made edematous (4,13,15) and the well-known clinical observation that an increase in transmission of high-frequency sound occurs, giving rise to auscultatory signs such as "whispering pectriloquy" when the lung is consolidated in the presence of pneumonia (19). Furthermore, the strong frequency dependence of normalized attenuation indicates that the increase in attenuation with inflation at high frequencies is an intrinsic property of the lung tissue and not simply a manifestation of increased distance traveled by the sound waves.…”
Section: Discussionsupporting
confidence: 87%
“…A key aspect of our study design was to introduce sound directly to the lung surface, rather than via the airway, the route of entry for sound in most earlier studies using isolated lungs (8,17) or using intact animals (4,15) and humans (1,6,10). Although studies utilizing airway entry of sound report that lung inflation has an effect on the velocity of sound from its point of entry at the airway opening to the surface of the lung or chest wall, interpretation of results requires assumptions about the pathway that sound takes through the respiratory system (1,8).…”
Section: Critique Of Methodsmentioning
confidence: 99%
“…One possible option may be to compute the ratio between sound and flow. Alternatively, a different approach based on the injection of a known sound and recording of the sound transmitted to the chest wall [46,47] may be applied, but this method may be less practical in critical care.…”
Section: Discussionmentioning
confidence: 99%
“…(23) One group of authors (24) measured the wet-to-dry weight ratio in pigs and observed that this ratio increased significantly in the group that received OA, compared with the control group, which suggests worsening of compliance. Using forced oscillation, the authors of another study (25) demonstrated an increase in airway opening pressure, although without stabilization for up to 140 min. The principal events responsible for the increase in compliance are the accumulation of liquid in the alveolar and interstitial space and the increase in surface tension.…”
Section: Resultsmentioning
confidence: 98%